2018
DOI: 10.1007/s00484-018-1548-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient education and rehabilitation after hip arthroplasty in an Italian spa center: a pilot study on its feasibility

Abstract: Nowadays, some spa centers are suitable for providing rehabilitative and preventive treatment in association with traditional spa therapy. This study aims to evaluate the feasibility and the effectiveness of an intensive rehabilitation program after hip arthroplasty in an Italian spa center. Early after total hip arthroplasty for severe osteoarthritis (≤ 10 days after the intervention), 12 consecutive patients (5 males and 7 females) aged between 50 and 85 years were enrolled for this study. All the patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
2
21
0
3
Order By: Relevance
“…Our results support the role of aquatic thermal therapy in the rehabilitation process of this population. Thermal hydrokinesitherapy may improve mood, anxiety and stress management, reduce fatigue and pain and thus facilitate rehabilitation (Oláh et al 2011;Musumeci et al 2018) without no reported side effects. Stress has a direct association with fatigue, which relates to pain (Rapolienė et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the role of aquatic thermal therapy in the rehabilitation process of this population. Thermal hydrokinesitherapy may improve mood, anxiety and stress management, reduce fatigue and pain and thus facilitate rehabilitation (Oláh et al 2011;Musumeci et al 2018) without no reported side effects. Stress has a direct association with fatigue, which relates to pain (Rapolienė et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment consisted of six sessions/week for 2 consecutive weeks of two and half hours of land-based (1 hour and a half) and hydrokinesitherapy (1 hour) with active and passive joint mobilization, respiratory and functional re-education exercises, gait and balance training, resistance exercise, and power training associated with physical therapy (electrotherapy and low-level-laser therapy). An educational program was provided to participants and families (Musumeci et al 2018). All subjects were evaluated the day of admission (T0) and at the end of treatment (T1); after 3 months (T2) and 6 months after the end of the treatment (T3) scales scores were collected by telephone interview.…”
Section: Methodsmentioning
confidence: 99%
“…The SF‐12 has also been shown to be able to discriminate between patients with rheumatoid arthritis of the hands/wrists who have high pain and those with low pain (PCS ES = 0.81 and MCS ES = 0.33) . In addition, the responsiveness of the SF‐12 to a wide range of treatments and programs for musculoskeletal conditions has been reported .…”
Section: Medical Outcomes Study 12‐item Short Form Health Surveymentioning
confidence: 96%
“…The applications of this system potentially range from rehabilitation to athletic training and research in the field of aquatic kinematics. Given that biofeedback allows faster and more effective recovery, with a pronounced proprioceptive nuance, the applications of wearable biofeedback suit in human rehabilitation can be envisaged in: orthopedic and rheumatic diseases [38], accompanied by general symptomatology -subacute and chronic pain syndromes, reduction of ROM, post-lesion recovery of soft tissue or bone and postoperative recovery [39]; scoliosis and pain management, especially in back pain; sports traumatology and spine trauma. With neurological diseases -where both biofeedback and the microgravity condition of water immersion (which allows movement even in the presence of significant deficits of motor units recruitment) find precise indications, wearable biofeedback suit would, for example, allow biofeedback-assisted aquatic step training in post-stroke [40] and hemiplegic patients [41], in para and tetraplegia and in Parkinson's disease [42], [43].…”
Section: Discussionmentioning
confidence: 99%